Effect of the use of fertilizer (APPETIZER) in the growth and yield of different varieties of potatoes Solanum tuberosum L - Al - Hamdani, Sobeih Abdul Wahab; Ibrahim, Ammar Jabbar behind (Journal of agricultural, environmental and veterinary sciences, 2018)
The experiment was conducted during the spring planting season 2017 In the Baquba nursery of Diyala Agriculture Directorate- Diyala Governorate. The study included three varieties of potatoes (AXENIA، OSIRIS and HERMES) And four concentrations of seaweed extract (APPETIZER) (0، 0.75، 1.5 and 2.25 ml. L-1) and with three spray. In order to study the effect of the variety and the concentration of seaweed extract in the growth and yield of potatoes. The trial included 12 treatments resulting from the combination of the study factors mentioned above. and applied Randomized complete Block Design (R.C.B.D) With three replicates، were statistical analysis using a program (SAS) The averages were compared using the Dunkin multiple rang test at 5%. The results showed that OSIRIS was significantly higher in the number of leaves، Leaves Area and chlorophyll، HERMES was significantly in the Plant Height، Leg diameter، While both was significantly in Number of legs. The concentration of 1.5 ml-1 water from the marine seaweed extract (APPETIZER) was significantly higher in the studied traits as well as significant differences during the interaction of the factors under study.